2020
DOI: 10.1111/aab.12612
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effects on plant reproductive organs: Physiological, productive, evolutionary and ecological aspects

Abstract: Studies involving the effects of long‐term exposure of plants to cadmium (Cd) are not usual, hence, data about Cd‐induced impacts on plant reproductive organs are scarce. The lack of robust information about this matter is surprising and also worrying because it is not yet clear whether (and how strong) Cd influences yield, and quality of fruits and seeds. Such information is necessary to guide strategies to manage crops and to avoid negative impacts on the environment and human health. This review gathers inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 111 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…Thus, Zn is needed in metabolically active differentiating cells that will form root and shoot tissues in the developing seedling. High metal(loid) concentrations in seeds are also critically important for the protection of germinating seeds and developing seedlings against infection by soil‐borne and seed‐borne pathogens, especially under environmentally stressful conditions (Carvalho et al., 2020 ; Carvalho et al., 2020 ; Ozturk et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zn is needed in metabolically active differentiating cells that will form root and shoot tissues in the developing seedling. High metal(loid) concentrations in seeds are also critically important for the protection of germinating seeds and developing seedlings against infection by soil‐borne and seed‐borne pathogens, especially under environmentally stressful conditions (Carvalho et al., 2020 ; Carvalho et al., 2020 ; Ozturk et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted on Andrographis paniculata , Cd suppressed the reproductive growth by decreasing the number in the inflorescence branch, flower, and flower buds, and also suppressed the fresh weight of the inflorescence and flower bud ( Patel, 2006a ). Cadmium affects the production and allocation of amino acids and sugars, absorption, assimilation, and distribution of nutrients in plants ( Carvalho et al., 2021 ). The fruit number and the fruit biomass has reported to be reduced in Adhatoda vasica L. grown in Cd treated soil when compared to control.…”
Section: Cadmium Toxicitymentioning
confidence: 99%
“…The results indicated that at low concentration, a positive effect was observed, while higher concentration was toxic to both species (Molnár et al, 2020), which also confirms the hormetic effect by NPs (Carvalho, Castro, & Azevedo, 2020). In a similar manner, it must be borne in mind that degrees of plant tolerance to toxic metals may also be associated with differential changes in essential macroelement and microelement, which can modulate physiological and developmental events (Carvalho, Gaziola, Carvalho, & Azevedo, 2020). When evaluated under higher concentrations, B. juncea showed higher tolerance to Zn‐NPs.…”
Section: Nps Applied To Plantsmentioning
confidence: 99%